Implementation of thirst management in the immediate postoperative period guided by knowledge translation and exchange - Carvalho, Isadora Pierotti; Garcia, Aline Korki Arrabal; Conchon, Marília Ferrari; Nascimento, Leonel Alves do; Santos, Robertha Pickina; Fonseca, Lígia Fahl (Revista Gaúcha de Enfermagem, 2025)
ABSTRACT Objective: To evaluate the implementation of the Thirst Management Model in the immediate postoperative period guided by the Knowledge Translation framework. Method: A quasi-experimental study, in the Post Anesthesia Care Unit of a large university hospital in northern Paraná. Implementation took place in two phases: preparation and implementation and change. Data was collected by observing the practice of nursing professionals. The implementation process was evaluated by measuring adoption and aspects of fidelity, using descriptive analysis of the level of adherence to the evidence in the continuous improvement cycles and the reach of the target audience. The adoption of the Thirst Management Model at pre- and post-implementation times was compared using Chi-square. Results: In the pre-implementation period, 236 events in the care provided by nursing professionals related to thirst management were observed, and 198 in the post-implementation period. Adoption of the evidence went from 28.2% pre-implementation to 78.4% post-implementation (p<0.001). The level of adherence exceeded the 70% target in one of the three cycles: 61.1%, 66.6%, 84.0%. The target audience was reached 100% in the first rapid cycle. Conclusion: The use of the theoretical framework and its multifaceted intervention significantly increased the adoption of the Thirst Management Model. RESUMEN Objetivo: Evaluar la aplicación del Modelo de Gestión de la Sed en el postoperatorio inmediato guiado por Traducción e Intercambio de Conocimientos. Método: Estudio cuasiexperimental pre y postest realizado en la sala de recuperación anestésica de un gran hospital universitario del norte de Paraná. La aplicación se llevó a cabo en dos fases: preparación y aplicación y cambio. Los datos se recogieron observando la práctica de los profesionales de enfermería. El proceso de implantación se evaluó midiendo la adopción y aspectos de fidelidad, mediante análisis descriptivo del nivel de adherencia a la evidencia en los ciclos de mejora continua y el alcance del público objetivo. La adopción del Modelo de Gestión de la Sed en los momentos pre y post-implementación se comparó mediante Chi-cuadrado. Resultados: En la preimplementación se observaron 236 eventos en la atención brindada por profesionales de enfermería relacionados con el manejo de la sed y 198 en la postimplementación. La adopción de las pruebas pasó del 28,2% antes de la implantación al 78,4% después (p<0,001). El nivel de adhesión superó el objetivo del 70% en uno de los tres ciclos: 61,1%, 66,6%, 84,0%. El público objetivo se alcanzó en un 100% en el primer ciclo rápido. Conclusión: El uso del marco teórico y su intervención multifacética condujeron a un aumento significativo de la adopción del Modelo de Gestión de la Sed. RESUMO Objetivo: Avaliar a implementação do Modelo de Manejo da Sede no pós-operatório imediato guiada pela Tradução e Intercâmbio do Conhecimento. Método: Estudo quase-experimental, pré e pós-teste, realizado na Sala de Recuperação Anestésica de um hospital universitário de grande porte no norte do Paraná. A implementação aconteceu em duas fases: preparação e implementação e mudança. Os dados foram coletados por meio da observação da prática dos profissionais de enfermagem. Avaliou-se o processo de implementação através da mensuração da adoção e aspectos da fidelidade, utilizando-se análise descritiva do nível de adesão à evidência nos ciclos de melhoria contínua e alcance do público-alvo. Comparou-se a adoção do Modelo de Manejo da Sede nos momentos pré e pós-implementação por meio do Qui-quadrado. Resultados: Na pré-implementação, 236 eventos na assistência prestada pelos profissionais de enfermagem relacionados ao manejo da sede foram observados e 198 na pós-implementação. A adoção da evidência foi de 28,2% pré-implementação para 78,4% pós-implementação (p<0,001). O nível de adesão superou a meta de 70% em um dos três ciclos: 61,1%, 66,6%, 84,0%. O alcance do público-alvo foi de 100% no primeiro ciclo. Conclusão: Utilizar o arcabouço teórico e sua intervenção multifacetada proporcionou aumento significativo na adoção do Modelo de Manejo da Sede.